Saccade-vergence properties remain more stable over short-time repetition under overlap than under gap task: a preliminary study - Lang, Alexandre; Gaertner, Chrystal; Ghassemi, Elham; Yang, Qing; Orssaud, Christophe; Kapoula, Zoï (Frontiers in Human Neuroscience, 2014)
Under natural circumstances, saccade-vergence eye movements are among the most frequently occurring. This study examines the properties of such movements focusing on short-term repetition effects. Are such movements robust over time or are they subject to tiredness ? Twelve healthy adults performed convergent and divergent combined eye movements either in a gap task (i.e., 200 ms between the end of the fixation stimulus and the beginning of the target stimulus) or in an overlap task (i.e., the peripheral target begins 200 ms before the end of the fixation stimulus). Latencies were shorter in the gap task than in the overlap task for both saccade and vergence components. Repetition had no effect on latency, which is a novel result. In both tasks, saccades were initiated later and executed faster (mean and peak velocities) than the vergence component. The mean and peak velocities of both components decreased over trials in the gap task but remained constant in the overlap task. This result is also novel and has some clinical implications. Another novel result concerns the accuracy of the saccade component that was better in the gap than in the overlap task. The accuracy also decreased over trials in the gap task but remained constant in the overlap task. The major result of this study is that under a controlled mode of initiation (overlap task) properties of combined eye movements are more stable than under automatic triggering (gap task). These results are discussed in terms of saccade-vergence interactions, convergence-divergence specificities and repetition versus adaptation protocols.